The Role of the Grade Ranking in University Admission: Between Haste and Uncertainty (Observatorio Económico, 2013)
Everything indicates that the selection factor for admission to the universities of the Council of Rectors of Chilean Universities (CRUCH), known as the “graderanking,” will have to be taken into account from now on. Beyond how it is calculated, the essential point to highlight is the major shortcomings that appear to afflict the arguments and the prior studies commissioned by the Council of Rectors. Continue reading...
Keywords: Higher education; Grade ranking